Depression and suicidal ideation among undergraduate medical students in Selangor, Malaysia - Cheng, Chong Rong; Kahar, Rojanah; Syed Alwi, Syarifah Maisarah (Human Resource Management Academic Research Society (HRMARS), 2024)
Suicidal ideation is prevalent among medical students which can significantly hamper their life span development and overall quality of life. A host of psychological illnesses such as depression have been identified to contribute to this high prevalence. This study aimed to investigate the relationship between depression and suicidal ideation among medical students in Selangor, Malaysia. A total of 217 medical students participated in this cross-sectional study. The instruments used to measure depression and suicidal ideation were the Patient Health Questionnaire-9 (PHQ-9) and the Beck Scale of Suicidal Ideation (BSS), respectively. Data were analysed using independent sample t-tests and Pearson’s correlation. 59.9% of our medical students demonstrated moderate to severe levels of depression. About two-thirds (66.8%) of the participants demonstrated moderate to high levels of suicidal ideation. Depression was strongly correlated with suicidal ideation. There was a significant gender difference in depression but no significant gender differences in suicidal ideation. This study provided insights and knowledge on the importance of mental health literacy, early detection, and tailored intervention of depression and suicidal ideation among medical students.